Profile of Critical Thinking Skills Associated with Science Learning Outcomes of Junior High School Students in Mataram City - Sari Hidayani; J. Jamaluddin; Agus Ramdani (Universitas Pendidikan Mandalika, 2020)
Efforts to develop critical thinking skills are still educational goals which are expected to improve learning outcomes which have an impact on the performance and quality of students. It is important to measure critical thinking skills so that the right techniques can be found to develop and improve these thinking skills. This study aims to describe critical thinking skills and their relationship with science learning outcomes of SMPN students in the city of Mataram. This type of research is a quantitative descriptive study with a sample of 418 Grade VII students and 435 Grade VIII students who were determined using purvosive techniques. Collecting data using test instruments that have been validated by experts and tested for reliability. The results showed that the critical thinking skills profile of the students of SMPN Mataram City was classified as moderate, with an average score of 68.83 for grade seven (VII) and 70.69 for grade eight (VIII). So it can be said that the relationship between critical thinking skills and science learning outcomes is very low as indicated by the R square value. R square for class VII is 0.074, which means that critical thinking skills have an effect of 7% on science learning outcomes. R square for class VII is 0.097, which means that critical thinking skills have an effect of 9% on science learning outcomes. The critical thinking skills of SMPN students in Mataram City needs to be improved by improving the learning process and learning evaluation tools.